2022
DOI: 10.1155/2022/1783392
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Contributing Factors on Aggressive Driving Based on a Structural Equation Model

Abstract: Tailored countermeasures that may significantly improve road traffic safety can be proposed and implemented if the relationship between various associated factors and aggressive driving is well understood. However, this relationship remains unknown, as driving behavior is complex, and the interrelationships among variables are not easy to identify. Considering this situation, this paper constructed a model based on a structural equation model (SEM) and factor analysis (FA), which is a multivariate statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Concerning the precipitation, no precipitation did not increase the likelihood of aggressive driving, but an insignificant amount of precipitation did. Xu et al's (2022) research also confirmed that adverse weather conditions, such as rain and fog, can amplify drivers' anxiety and contribute to aggressive driving behavior. One possible explanation is that the noise and low visibility on rainy days are disturbing and irritating.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Concerning the precipitation, no precipitation did not increase the likelihood of aggressive driving, but an insignificant amount of precipitation did. Xu et al's (2022) research also confirmed that adverse weather conditions, such as rain and fog, can amplify drivers' anxiety and contribute to aggressive driving behavior. One possible explanation is that the noise and low visibility on rainy days are disturbing and irritating.…”
Section: Resultsmentioning
confidence: 88%
“…The establishment of the model is also relatively simple. In addition to simple statistical analysis, traditional statistical models such as logistic regression (Oh & Jang, 2017), discrete choice models (Feng et al, 2012), and structural equation models (Xu et al, 2022) are also used.…”
Section: Influencing Factors Of Aggressive Drivingmentioning
confidence: 99%